Why be happy when you could be normal? - Winterson, Jeanette, 1959- (Grove Press, 2011)
This memoir is a tough-minded search for belonging, for love, an identity, a home, and a mother by the author of "Oranges Are Not the Only Fruit"--winner of the Whitbread First Novel award and the inspiration behind the award-winning BBC television adaptation "Oranges."